KEDUDUKAN BEZITER TERHADAP TANAH AKIBAT DALUARSA - Farhan Daffa Ramadhan (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this study is to analyze the status of a land bezitter in Decision No. 2778/KPdt/2013 to obtain property rights that have been or are being occupied by way of expiration and efforts to protect the bezitter's legal protection of the land hereinafter referred to as disputed land. The method in this research is normative juridical, namely through the study of legislation supported by secondary materials. The results of the study found that one way to obtain recognition of the acquisition of property rights is through acquisitive verjaring. This method allows a person to obtain land rights in good faith due to expiration In article 1963 Kuhper expiration as a way of acquiring something, namely, "Who in good faith, and based on a valid basis, acquires an immovable object, an interest, or another receivable that does not have to be paid on appointment, acquires property rights over it, by way of expiration, with a twenty-year possession. Whoever in good faith controls it for thirty years, acquires the right of ownership, without being forced to show the basis of the right." In Decision No. 2778/K/PDT/2013, the defendant should have been able to obtain his rights because he had controlled the land hereinafter referred to as the disputed land for 38 (thirty-eight years) and in good faith, which was in accordance with the method of obtaining land through expiration.